Respuesta :

[tex]\boldsymbol{\sqrt{\dfrac{p}{2}-2}=\sqrt{p-8}}[/tex]

Cancel the square root on both sides.

  • [tex]\boldsymbol{\sf{\dfrac{p}{-2}-2=\sqrt{p-8} }}[/tex]

Multiply both sides by 2.

  • [tex]\boldsymbol{\sf{p-4=2p-16 }}[/tex]

Subtract p from both sides.

  • [tex]\boldsymbol{\sf{-4=2p-16-p }}[/tex]

Simplify

  • [tex]\boldsymbol{\sf{-4=p-16 }}[/tex]

Add 16 to both sides.

  • [tex]\boldsymbol{\sf{-4+16=p }}[/tex]

Simplify

  • [tex]\boldsymbol{\sf{12=p}}[/tex]

Swap sides.

  • [tex]\boldsymbol{\sf{p=12 \ \ \to \ \ \ Answer}}[/tex]

Verification

[tex]\boldsymbol{\sqrt{\dfrac{p}{2}-2}=\sqrt{p-8} \ \ \to \ \ \ Exercise \ normal.}[/tex]

Let p=12.

  • [tex]\boldsymbol{\sqrt{\dfrac{12}{2}-2}=\sqrt{12-8}}[/tex]

Simplify 12/6 to 6.

  • [tex]\boldsymbol{\sqrt{6-4}=\sqrt{12-8} }[/tex]

Simplify 6-2 to 4.

  • [tex]\boldsymbol{\sqrt{4}=\sqrt{12-8} }[/tex]

Since 2×2=4, the square root of 4 is 2.

  • [tex]\boldsymbol{2=\sqrt{12-8} }[/tex]

Simplify 12-8 to 4.

  • [tex]\boldsymbol{2=\sqrt{4} }[/tex]

Since 2×2=4, the square root of 4 is 2.

  • [tex]\boldsymbol{2=2}[/tex]

Checked ✅

[tex]\huge \red{\boxed{\green{\boxed{\boldsymbol{\sf{\purple{Pisces04}}}}}}}[/tex]

2=2^
Explained above